2007
DOI: 10.1152/ajpregu.00767.2006
|View full text |Cite
|
Sign up to set email alerts
|

Denervation-induced skeletal muscle atrophy is associated with increased mitochondrial ROS production

Abstract: Van Remmen H. Denervation-induced skeletal muscle atrophy is associated with increased mitochondrial ROS production. Am J Physiol Regul Integr Comp Physiol 293: R1159-R1168, 2007. First published June 20, 2007; doi:10.1152/ajpregu.00767.2006.-Reactive oxygen species (ROS), especially mitochondrial ROS, are postulated to play a significant role in muscle atrophy. We report a dramatic increase in mitochondrial ROS generation in three conditions associated with muscle atrophy: in aging, in mice lacking CuZn-SOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
290
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 301 publications
(314 citation statements)
references
References 88 publications
16
290
3
5
Order By: Relevance
“…Although loss of catalytic hSOD1 activity has been implicated and mitochondrial ROS is associated with the mechanism underlying denervation-induced atrophy (Muller et al, 2007) in familial ALS, the nature of the toxicity is poorly understood (Carri et al, 1997;Kruman et al, 1999;Rizzardini et al, 2005). Evidence for mutations in SOD1 as driving the pathogenesis of ALS has been reported in cell systems and mice overexpressing the hSOD1 G93A protein as described above (Jung et al, 2002;Mali and Zisapels, 2008;Mattiazzi et al, 2002;Vijayvergiya et al, 2005).…”
Section: Genetic-linked Alterations In Lactate Homeostasis Underlyingmentioning
confidence: 99%
“…Although loss of catalytic hSOD1 activity has been implicated and mitochondrial ROS is associated with the mechanism underlying denervation-induced atrophy (Muller et al, 2007) in familial ALS, the nature of the toxicity is poorly understood (Carri et al, 1997;Kruman et al, 1999;Rizzardini et al, 2005). Evidence for mutations in SOD1 as driving the pathogenesis of ALS has been reported in cell systems and mice overexpressing the hSOD1 G93A protein as described above (Jung et al, 2002;Mali and Zisapels, 2008;Mattiazzi et al, 2002;Vijayvergiya et al, 2005).…”
Section: Genetic-linked Alterations In Lactate Homeostasis Underlyingmentioning
confidence: 99%
“…A very interesting experimental study announced that denervation-induced atrophy was associated with a 30-fold increasing on mitochondrial free radical production (Muller et al 2007). In animal models of sarcopenia it has been suggested that both defective mitochondria and SOD deficiency in senescent skeletal muscle cells resulted in massive release of superoxide anion which decisively contributes to aging-related sarcopenia (Jackson 2009).…”
Section: Tac In Aging and Detraining: Is The Lack Of Exercise The Orimentioning
confidence: 99%
“…For example, transgenic mice overexpressing catalase showed the entire spectrum of responses: (1) a substantial increase in lifespan (Schriner et al 2005), (2) no change in lifespan (Chen et al 2004;Huang et al 2000), or (3) were more vulnerable to oxidative insults (Chen et al 2004). Overexpression of Cu/Zn SOD in several studies did not influence lifespan Muller et al 2007b). Furthermore, heterozygous knockouts for MnSOD, while showing reduced enzyme activity, have a similar lifespan to that exhibited by wild-type mice, even though oxidative damage in several tissues (e.g., 8oxodG in liver, heart, brain, spleen) is significantly elevated (Van Remmen et al 2003).…”
Section: Do Long-living Animals Produce Less Ros Than Shorter-living mentioning
confidence: 99%